Differences Between NRS-2002 and MUST in Relation to the Metabolic Condition of Trauma Patients - Oktaffrastya Widhamurti Septafani; Suharto Suharto; Harmayetty Harmayetty (Jurnal Ners, 2018)
Introduction: Flow phase with high cardiac output and increased metabolic conditions. When metabolic conditions are not stable there will be a long duration of complications until death. One of the benefits of Nutrition Risk Screening (NRS-2002) is reliable inpatient care for critical patients. While the Malnutrition Universal Screening Tool (MUST) shows speed in the classification of nutritional disorders.Methods: This study used the observational design method. The sampling technique in this study used Consecutive sampling in accordance with the criteria consisting of 31 respondents. This was to determine the specificity and sensitivity values of NRS 2002 and MUST using contingency table analysis and for the Area Under Curve (AUC) using Receiver Operating Characteristic (ROC) curve analysis.Results: The sensitivity values in MUST was predicted for metabolic conditions which was higher than when using NRS 2002, but the specificity and value of AUC (Area Under Curve) was higher using NRS 2002 than using MUST when it came to predicting metabolic conditions.Conclusions: There were differences in effectiveness between use of Nutritional Risk Screening (NRS-2002) with the Malnutrition Universal Screening Tool (MUST) in relation to changes in metabolic conditions of trauma patients. NRS-2002 is more effective than MUST. NRS 2002 has the ability to identify patients more precisely who are likely to have a negative outcome.